Rumah Apotek Hidup Kampung Konservasi Toga Untuk Mengembangkan Ekonomi Produktif Di Desa Getas - Aliffadjri Gimnastiar; Teodora M.F.B. Da Silva; Arum Wahyuningsih; Hany Dwi Kurnia; Muftichatun Muftichatun; Ratna Trianingsih; Ahmad Nabil Al Aflah; Ansgarius Fareri; Bagus Tegar Ardi Pramana; Eloi Noni Krismiyadi Tloim; Fadhila Inas Zhafira; Khairun Nisa Aristiyanti; Law Bennett Valorie Laurent; Muhammad Agus Niam; Nur Rizki Kodijah; Ulin Nuha Billangga (Jurnal Kabar Masyarakat, 2023)
Getas Village, Singorojo District, Kendal Regency, is a village located on a plateau with an altitude of 378 meters above sea level (masl) with a village area of ​​17.90 km2. The beautiful air and fertile soil make plantations the main commodity of this village and most of the local people work as farmers. However, the problems that the people of Getas Village have to face are the lack of community access to health facilities, medicines and shopping centers, as well as the lack of support and attention from the government in providing resources and funds for cultivating medicinal plants. The aim of the activities carried out is to cultivate Toga or family medicinal plants in the Getas Village community and to establish a herbal medicine business processing medicinal plants with the brand "Soe D'jamoe". In carrying out this program the PPK Ormawa team introduced toga using toga and hydroponic socialization methods. We also provide training to the Getas Village community about greenhouse management, making organic fertilizer and making toga products, as well as marketing them.